Viaduct in the highway siervo de la nación - Santos, Carlos (2018)
The aim of this paper is to present a real case study regarding the long multi-span viaducts. Briefly, the authors show the global structural concept used in Mexico City's long viaduct to ensure a good behavior to accommodate differential settlements that can occur. It is important to highlight that the design was developed by GEG.